2020
DOI: 10.1186/s13006-020-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a high-fidelity lactation simulation model for health professional breastfeeding education

Abstract: Background: A key reason for premature cessation of breastfeeding is inadequate support from healthcare providers. Most physicians and nurses do not feel confident in their ability to support families with breastfeeding initiation or maintenance. Increasing health professional confidence in clinical lactation skills is key to improving maternal and child health outcomes. High-fidelity (realistic) simulators encourage learner engagement, resulting in increased clinical skills competency, confidence, and transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
20
0
5
Order By: Relevance
“…During a development trial, physician residents reported benefits of being able to practice comfortable hand positioning during the breast assessment. Breastfeeding medicine physicians and midwifery students evaluated the final model as having realistic representations of lactation-related pathology and an effective breast pump mechanism to simulate hand expressing [37].…”
Section: Improving Breastfeeding Educationmentioning
confidence: 99%
“…During a development trial, physician residents reported benefits of being able to practice comfortable hand positioning during the breast assessment. Breastfeeding medicine physicians and midwifery students evaluated the final model as having realistic representations of lactation-related pathology and an effective breast pump mechanism to simulate hand expressing [37].…”
Section: Improving Breastfeeding Educationmentioning
confidence: 99%
“…One student was removed from all analyses, as she did not have a partner for the OSCE and talked through the case instead of performing the skills. Additional demographic information has been described elsewhere [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The participants agreed (5.9/7) the expert in-room facilitator provided tangible and realistic suggestions for improvement. The participants ( n = 7) indicated that the LSMs are made very well, improved the realism of the encounter (5.7/7), and they were key for supporting hands-on practice in clinical lactation [ 12 ]. During the focus group, the participants indicated that role-playing is a great modality for learning because of the ability to practice being face-to-face with a mock breastfeeding patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further effectiveness differs by provider type (Balyakina et al, 2016; Uzumcu et al, 2020; Wallenborn et al, 2018) with women receiving prenatal care from obstetricians less likely to sustain breastfeeding, possibly due to different training, or workload, or competing priorities (Garner et al, 2016; Rosen-Carole et al, 2020), especially in practices that primarily serve women from lower income households (Havens & Wines, 2019; Qureshey et al, 2020; Shen & Rudesill, 2016). Many obstetric providers express interest in initiatives to improve their patients’ breastfeeding rates; more efficient methods for implementing the ACOG recommendations are needed (Lutenbacher et al, 2016; Rosen-Carole et al, 2020; Sadovnikova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%